2010
DOI: 10.1007/s12010-010-9014-0
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Production by Solid Substrate Fermentation of Pleurotus ostreatus and Trametes versicolor on Tomato Pomace

Abstract: A process of solid state fermentation (SSF) on tomato pomace was developed with the white-rot fungi Pleurotus ostreatus and Trametes versicolor, using sorghum stalks as support. Operative parameters (humidity, water activity, and size of substrate particles) guaranteeing a good colonization of tomato pomace by both fungi were defined and conditions for production at high titers of the industrially relevant enzymes laccase, xylanase and protease were identified. Significant laccase activity levels (up to 36 U g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…Several of these factors have been genetically mapped as activity QTLs (44). Laccase activity values recorded for the SSF cultures were similar to others reported for Pleurotus species growing in similar substrates (3) but lower than those reported for SSF cultures made using agricultural wastes (16,45).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several of these factors have been genetically mapped as activity QTLs (44). Laccase activity values recorded for the SSF cultures were similar to others reported for Pleurotus species growing in similar substrates (3) but lower than those reported for SSF cultures made using agricultural wastes (16,45).…”
Section: Discussionsupporting
confidence: 80%
“…4). Unk1 had been recently described in a study of SSF cultures performed using tomato pomace (16), and it appeared to be abundant under the SSF conditions used in our study, which were more similar to the natural environmental conditions under which P. ostreatus grows than the conditions used for the submerged cultures. Interestingly, expression of this isoform does not appear to be induced by the wheat straw extract and consequently could be associated with the physical culture conditions, rather than with the presence of phenolic inducers.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…All cellulase activities were stable at 40 and 50 °C through 48 h of pre-incubation. Iandolo et al (2011) reported the activity of three enzymes from Pleurotus ostreatus and Trametes versicolor grown on tomato pomace using sorghum stalks as support. Laccases, proteases, and xylanases activities were 36, 34000, and 50 U/g dry matter, respectively, while Pleurotus ostreatus produced approximately half of those values.…”
Section: Resultsmentioning
confidence: 99%
“…A maximum laccase activity production level of 15 U g -1 dry wt. was achieved at the third to fourth day of P. ostreatus SSF on tomato pomace 37 . Isikhuemhen and Mikiashvilli 38 reported the highest laccase activity of 164.6 U g -1 of P. ostreatus MBFBL400 on SSF of wheat straw and solid waste from anaerobic digestion of litter mixture.…”
Section: Confirmation Testmentioning
confidence: 95%